The effect of synbiotic supplementation on anthropometric indices, appetite, and constipation in people with hypothyroidism: A randomized, double‐blind, placebo‐controlled trial - Talebi, Sepide; Karimifar, Mozhgan; Heidari, Zahra; Mohammadi, Hamed; Asbaghi, Omid; Hadi, Amir; Marx, Wolfgang; Askari, Gholamreza (Phytotherapy research, 2020)
Abstarct Hypothyroidism and obesity are two highly prevalent conditions that appear to be closely related. Hypothyroidism is correlated with weight gain, loss of appetite, constipation, and a higher incidence of obesity. The present study aimed to investigate the effects of synbiotic supplementation on anthropometric indices, appetite, and constipation in subjects with hypothyroidism. Sixty subjects with hypothyroidism were assigned into two groups to receive either 500 mg/day of synbiotic (n = 30) or a placebo (n = 30) per day for 8 weeks. Anthropometric indices, appetite, and constipation were assessed at study baseline and end of the trial. At the end of trial, waist‐to‐hip ratio was significantly decreased in the synbiotic group (p = .030), whereas there were no significant differences between groups. We did not observe any statistically significant change in appetite or other anthropometric indices (p > .05). Compared with the placebo synbiotic supplementation led to a significant reduction in constipation (p = .048). The results of the present trial indicated that synbiotic supplementation may have favorable results in constipation among subjects with hypothyroidism for 8 weeks. Further studies with larger sample size and longer duration are needed to confirm our findings.